2005
DOI: 10.1021/jm0503648
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Poly(acrylic acid) Acceleration of Antithrombin Inhibition of Thrombin:  Implications for the Design of Novel Heparin Mimics

Abstract: The bridging mechanism of antithrombin inhibition of thrombin is a dominant mechanism contributing a massive ∼2500-fold acceleration in the reaction rate and is also a key reason for the clinical usage of heparin. Our recent study of the antithrombin-activating properties of a carboxylic acid-based polymer, poly(acrylic acid) (PAA), demonstrated a surprisingly high acceleration in thrombin inhibition (Monien, B. H.; Desai, U. R. J. Med. Chem. 2005, 48, 1269. To better understand this interesting phenomenon, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Small non-carbohydrate motifs (Ͻ1000 Da) have shown promise (20,32,37), but targeting the PBS has proved to be difficult (19,42). Larger non-carbohydrate motifs of the size of heparin (or LMWH) are difficult to design (33,34) or find in nature. Only a couple of natural non-polysaccharide, macromolecular structures, condensed tannins and lignins (28,29), are known that can be exploited for binding to highly electropositive-binding sites on proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Small non-carbohydrate motifs (Ͻ1000 Da) have shown promise (20,32,37), but targeting the PBS has proved to be difficult (19,42). Larger non-carbohydrate motifs of the size of heparin (or LMWH) are difficult to design (33,34) or find in nature. Only a couple of natural non-polysaccharide, macromolecular structures, condensed tannins and lignins (28,29), are known that can be exploited for binding to highly electropositive-binding sites on proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These free energies of binding are significantly higher than those of the monomeric or oligomeric non-carbohydrate ligands studied to date. For example, the polyacrylic acids displayed binding energies between 5.1 and 6.1 kcal/mol at pH 7.4, I 0.05, 25°C, whereas ⌬G 0 for small aromatic sulfates was in the range of 4.2-5.3 kcal/mol at pH 7.4, I 0.15, 25°C (19,(32)(33)(34). With respect to comparable polysaccharide ligands, these affinities are only 4 -32-fold weaker.…”
Section: A Specific Sulfated Dhp Sdso3 Preferentially Inhibits Factmentioning
confidence: 99%
See 2 more Smart Citations
“…S3). PAA is used during nanoparticle synthesis to enable easy collection and subsequent resuspension of particles, and also has been implicated as an anticoagulant (21). In our small-scale study, we found that particles with PAA were at least as effective as particles made without PAA at reducing lethality, and thus we used PAA in all subsequent work.…”
Section: Investigating the Role Of Hemostatic Nanoparticles On Lethalitymentioning
confidence: 93%